Manajemen Strategik Gerakan Sekolah Menyenangkan Dalam Mewujudkan Profil Pelajar Pancasila - Purwaningsih Purwaningsih; Imam Mawardi; Nurodin Usman (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2023)
Research Objectives :(1) To find out the strategic management planning of the fun school movement in realizing the Pancasila student profile; (2) To find out the strategic management process of the fun school movement in realizing the Pancasila Student profile; (3) To compile a strategic management evaluation of the fun school movement in realizing the Pancasila Student profile. The method used is descriptive, data obtained through interviews, document study and observation. The results of the study show that the strategic management of the fun school movement in realizing the Pancasila student profile is carried out in three stages, namely: planning, implementation and evaluation. Strategic management planning is carried out superiorly by identifying opportunities and threats from outside as well as strengths and weaknesses from within the school or analyzing the external and internal environment, determining the GSM strategy; Explanation of the vision, mission and objectives that have been implemented as well as identification of short, medium and long term plans. Implementation is carried out by determining academic planning in schools including compiling and implementing programs, compiling budgets, motivating educators and education staff, allocating human resources so that the strategies that have been implemented can be implemented and developing a school culture that supports the fun school movement strategy in realizing student profiles pancasila. Management evaluation is carried out in three ways, namely direct evaluation of school programs or activities, evaluation of the academic field and evaluation meetings.